An experimental study on breast cancer discrimination using metasurface-based microwave technology - Kyrillos Youssef; Ahmed H. Abd El-Malek; Haruichi Kanaya; Mohammed Abo-Zahhad (Discover Applied Sciences)
Abstract Multifocal (MF) breast cancer tends to be more aggressive than unifocal (UF) ones, with higher probabilities of recurrence, lymph node metastases, and lower survival rates. Given the inherent limitations of current medical imaging techniques, there is a pressing need for the development of more precise and sensitive alternatives. Microwave imaging (MWI) has emerged as a promising method for breast cancer detection due to its portability, non-ionizing nature, and cost-effectiveness. To our knowledge, this is the first study aimed at distinguishing MF breast cancer from UF one using MWI. In our previously published theoretical paper [1], we introduced a $$2 × 2$$ 2 × 2 planar metasurface-based array antenna operating at 2.4 GHz to differentiate between these critical stages of breast cancer. In this experimental study, we aim to validate and extend those theoretical predictions through a series of meticulously designed experiments. Our experimental data strongly support the theoretical model. The performance of the proposed array is experimentally verified using an N5227A vector network analyzer (VNA). The arrayed antenna demonstrated full breast coverage, enhancing its sensitivity for detecting deeper tumors with a phase difference of $$11^{° }$$ 11 ∘ . Analysis of the phase shift across the $$S_{ij}$$ S ij parameters achieved a distinguishing level of $$29^{° }$$ 29 ∘ , highlighting its significant potential in addressing the spread of metastatic MF breast tumors.